Topic shift impairs pronoun resolution during sentence comprehension: Evidence from event‐related potentials. (23rd November 2015) - Xu, Xiaodong; Zhou, Xiaolin
Abstract: This study investigated how topic shift and topic continuation influence pronoun interpretation in Chinese. ERPs recorded on pronouns in topic structure showed stronger and earlier late positive responses (P600) for the topic‐shift than for the topic‐continuation conditions. However, in nontopic structure where the subject (denoting only subjecthood), rather than the topic (denoting both topichood and subjecthood), acted as the antecedent of the pronoun, almost indistinguishable P600 responses were obtained on the pronoun regardless of whether it was referring to the subject (i.e., subject continuation) or the object (i.e., subject shift). Moreover, stronger and earlier P600 responses were elicited by pronouns in the topic‐shift than in the subject‐shift conditions, although there was no difference between the topic‐continuation and the subject‐continuation conditions. These findings suggest that topic shift results in greater difficulty in the resolution stage of referential processing, although the bonding process is not sensitive to the manipulation of topic status, and that topic has a privileged cognitive status relative to other nontopic entities (e.g., subject) in real‐time language processing.